Il corpo umano nella cultura di massa - Pastucha-Blin, Agnieszka (Neophilologica, 2011)
The present contribution is an attempt to shed light on how the human body (it. corpo umano) is conceptualized in persuasive discourse, especially that addressed to women. The paper shows how the contemporary culture deifies the human body (corpo umano) which has become a cult object. Therefore the human body (corpo umano) becomes a body that is visualized, reproduced a number of times, often in an obsessive way, by the mass media. The contemporary cultural models consider the human body (corpo umano) a plastic substance, ready to be modelled, like a machine, treated in an instrumental or mechanic way, or as a complex system that is made of independent parts, which provokes an effect of splitting and multiplication. Although these models appear, they are definitely inappropriate with reference to most people’s body image.